2018
DOI: 10.3390/pharmaceutics10020060
|View full text |Cite
|
Sign up to set email alerts
|

A Repurposed Drug for Brain Cancer: Enhanced Atovaquone Amorphous Solid Dispersion by Combining a Spontaneously Emulsifying Component with a Polymer Carrier

Abstract: Glioblastoma multiforme (GBM) is the most common and lethal central nervous system tumor. Recently, atovaquone has shown inhibition of signal transducer and activator transcription 3, a promising target for GBM therapy. However, it is currently unable to achieve therapeutic drug concentrations in the brain with the currently reported and marketed formulations. The present study sought to explore the efficacy of atovaquone against GBM as well as develop a formulation of atovaquone that would improve oral bioava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Upregulated STAT3 contributes to tumorigenesis by increasing cancer proliferation, metastasis, drug resistance, and prevents apoptosis [129]. Atovaquone is found to inhibit STAT3 in thyroid cancer, acute myeloid leukemia (AML), and glioblastoma, therefore decreasing cell viability and inducing apoptosis in these cancers [87,90,91].…”
Section: Mechanism Of Action Of Anti-parasitic Drugsmentioning
confidence: 99%
“…Upregulated STAT3 contributes to tumorigenesis by increasing cancer proliferation, metastasis, drug resistance, and prevents apoptosis [129]. Atovaquone is found to inhibit STAT3 in thyroid cancer, acute myeloid leukemia (AML), and glioblastoma, therefore decreasing cell viability and inducing apoptosis in these cancers [87,90,91].…”
Section: Mechanism Of Action Of Anti-parasitic Drugsmentioning
confidence: 99%
“…The thermal shear caused by HME is not only capable of greatly increasing the degree of interaction between the drug and polymer but also gives rise to a dense and uniform matrix producing granules with excellent flow characteristics, as previously described [ 9 , 11 ].…”
Section: Resultsmentioning
confidence: 76%
“…Hot-melt extrusion (HME) has gained interest in the pharmaceutical field as a processing technology capable of producing solid dispersions with a high degree of drug-polymer interactions. The simultaneous mechanical and thermal shear of samples achieved by HME can noticeably modify drug properties such as solubility [ 9 ], poor taste, and flowability [ 10 ], while producing sustained drug delivery systems [ 11 ]. Moreover, the association of HME with computer-aided design and computer-aided manufacturing is expanding its medical potential in the production of prostheses and even in 3D printed drug products [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…ATO is structurally similar to coenzyme Q10 and competitively inhibits its binding to the cytochrome bc1 complex, resulting in mitochondrial membrane potential (MMP) collapse and parasite death (17). ATO has attracted attention as a novel anticancer agent for targeting various types of cancer cell (18)(19)(20)(21)(22). Ashton et al (23) revealed that ATO reduces the oxygen consumption rate by inhibiting mitochondrial respiration complex III activity, reduces hypoxia in both spheroids and xenografted tumors and causes tumor growth delay in combination with radiation.…”
Section: Introductionmentioning
confidence: 99%